Influence of chemical treatments on cellulose fibers for use as reinforcements in poly(ethylene‐co‐vinyl acetate) composites. Issue 7 (24th February 2015) - Zimmermann, Matheus V.G.; de Macedo, Vinícius; Zattera, Ademir J.; Santana, Ruth M.C.
Abstract : This work evaluates different chemical treatments on cellulose fibers as reinforcement agents in poly(ethylene‐vinyl acetate) (EVA) composites. The cellulose fibers were prepared with three chemical modifications using triethoxyvinylsilane, acetic anhydride (AA), and glycidyl methacrylate (GMA). Composites were prepared with 10 phr of cellulose fibers by means of extrusion and hot press conformation. The fiber treatment levels were successfully demonstrated through Fourier transform infrared spectroscopy with the appearance of characteristic bands in each chemical group, and scanning electron micrographs showed altered textures on the surfaces, polymerized material and fiber agglomerations after the chemical treatments that were most evident in the AA and GMA treatments. The composites reinforced with treated fibers showed improvement in their mechanical properties at the yield points and were reduced in deformation. When activated with dicumyl peroxide, the mechanical properties were even more improved and the interface regions exhibited better interactions between the cellulose fibers and the EVA matrix. POLYM. COMPOS., 37:1991–2000, 2016. © 2015 Society of Plastics Engineers